The qigong workbook for anxiety : powerful energy practices to rebalance your nervous system and free yourself from fear - Lam, Kam Chuen. (New Harbinger Publications, 2014)
" We live in a fast-paced, busy world, and many of us are stressed out and anxious as a result. If you suffer from anxiety but have found little relief from modern western treatments, or if you are looking for complimentary treatment, the ancient practice of qigong-which can be understood as the cultivation of internal energy-may offer you relief. Qigong is rooted in Chinese philosophy and medicine, and it utilizes breathing, movement, and awareness exercises to promote healing and aid in meditation. In The Qigong Workbook for Anxiety, world-renowned and respected qigong master Kam Chuen Lam presents the first workbook for overcoming anxiety problems utilizing traditional Chinese energy-focusing exercises. By following these simple and accessible step-by-step exercises, readers will learn to transform feelings of anxiety into resilience and inner strength. The workbook also contains helpful illustrations to help you carry out these exercises. In the book, Lam will help you think about anxiety, and yourself, in a different way-as a whole. You'll also learn to stop resisting moments of anxiety and other strong emotions, but rather to embrace them within the larger flow of your body's energy field. By doing this, you will ultimately strengthen and cultivate the natural energy you possess. Author Kam Chuen Lam has been a traditional Chinese healer for over forty years, and is an internationally respected authority on the Chinese health systems of Chi Kung and Tai Chi. To find out more, visit www.lamkamchuen.org"--